Molecular-biological markers for analysis of Gentoo penguin’s (Pygoscelis papua) genetic diversity from Antarctic Peninsula - Dranitsina, A. S.; Telegeev, G. D.; Dybkov, M. V.; Chumachenko, I. N.; Bezrukov, V. F. (Ukrainian Antarctic Journal, 2006)
The estimation of genetic polymorphism of Gentoo penguin (Pygoscelis papua) by RAPD markers has been carried out. RAPD analysis was used to examine the extent of genetic polymorphism in two populations of Gentoo penguin (Pygoscelis papua) from Antarctic Islands (Petermann and Livingston). RAPD-PCR analysis was carried out as the modified method of Operon. A series of random primers 10 bp each has 60-70% GC contents (OPA, OPM, OPP (Operon Technologies, Alameda, CA, USA)) (Mishta et al. 2002) and an original primer (11 mer) were used for RAPD analysis. For obtaining probes with (TTAGGG)n repeat the corresponding oligonucleotide (TTAGGG)3 and complementary them oligonucleotide (TAACCC)3 were synthesized. The primers were prepared for anneling and then ligated into pUC19 plasmid vector. The cloned fragment (450 bp.) was labeled with [α-Р32]-dCTP and DIG (digoxigenin) using forward and reverse standard primers in a polymerase chain reaction. The chosen three 10 mer oligonucleotide primers accordingly to preliminary results showed different levels of polymorphism in Gentoo penguins at Petermann Island (from 22,6% до 42,9%) and Livingston Island (from 41,3% до 57,1%). Nei’s similarity coefficients were in range from 0,561 (when Gentoo genome profiles were compared with RAPD profiles of two related penguin species: Pygoscelis adeliae (Adelie) and Pygoscelis antarctica (Chinstrap)) to 0,928 among observed Gentoo penguin populations. Nei’s distances values ranged from 0,075 to 0,579 among the populations and species. Accordingly to the obtain results it was proved that the examined populations belong to the same subspecies Pygoscelis papua ellsworthi. We determined the maximum (approximately 9000 bp) and the mean telomere length of Gentoo penguins approximately 6300±1256 bp for adult specimens and 8100±828,4 bp for chicks.